2016
DOI: 10.1186/s12879-016-1975-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and epidemiology of meningococcal carriage in Southern Ethiopia prior to implementation of MenAfriVac, a conjugate vaccine

Abstract: Background Neisseria meningitidis colonizes humans and transmits mainly by asymptomatic carriage. We sought to determine the prevalence and epidemiology of meningococcal carriage in Ethiopia prior to the introduction of MenAfriVac, a serogroup A meningococcal conjugate vaccine.MethodsA cross-sectional meningococcal carriage study was conducted in Arba Minch, southern Ethiopia. A total of 7479 oropharyngeal samples were collected from 1 to 29 year old volunteers, between March and October, 2014. The swabs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 58 publications
3
25
3
Order By: Relevance
“…No Nm A was detected. The diversity of the isolates remained low but higher than that recorded in the Burkina Faso studies .…”
Section: Resultscontrasting
confidence: 65%
See 3 more Smart Citations
“…No Nm A was detected. The diversity of the isolates remained low but higher than that recorded in the Burkina Faso studies .…”
Section: Resultscontrasting
confidence: 65%
“…Carriage of N. lactamica was also studied in a rural community in Ethiopia in 2014 . The prevalence of carriage in subjects aged 1–29 years was similar to that seen in Burkina Faso (28.1%) but, unlike the situation in Burkina Faso, varied significantly among districts (kebeles).…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…However, there should be other factors that control capsular switching between serogroup A and other N. meningitidis serogroups, such as the imbalanced carriage rate between different serogroups. The N. meningitidis ST-7 serogroup A strain was isolated less occasionally from healthy carriers than with other serogroups that are commonly related to invasive strains (21). Our recent investigation of meningococcal carriage also showed that N. meningitidis serogroup A was rarely detected even in a population with high incidence (data not published).…”
Section: Discussionmentioning
confidence: 79%